KEMAMPUAN MENULIS PUISI DENGAN MEDIA SOSIAL BEETALK SISWA KELAS VIII SMPN 2 PACIRAN KABUPATEN LAMONGAN - Tri Lestari, Laila (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2017)
Writing poetry is an activity embody the ideas, thoughts and feelings in a short, dense and multi meaning. This research is a class act. Therefore, the objectives of this research is to explain the process and outcome improvement ability to write poetry using social media Beetalk in learning Indonesian class VIII SMPN 2 Paciran. This research steps include; (1) plans to improve the action, (2) Measures in this study should be done with caution, (3) Observations on the implications of the action taken against the object of study and noted in observation, and (4) reflection. Based on the results of process analysis and the ability to write poetry with social media Beetalk increased. The results showed in the first cycle of students included in the high category in a developing theme number 8 from 25 students to 32% of that number increased to 100% in the high category in the second cycle. It showed an improvement in the theme of 68% in 17 students. I cycle quite reach the 12 categories from 25 students to 48% while the lower reaches category 5 students by 20%.